2014
DOI: 10.1002/jcp.24679
|View full text |Cite
|
Sign up to set email alerts
|

Pin1 Regulates Osteoclast Fusion Through Suppression of the Master Regulator of Cell Fusion DC‐STAMP

Abstract: Cell fusion is a fundamental biological event that is essential for the development of multinucleated cells such as osteoclasts. Fusion failure leads to the accumulation of dense bone such as in osteopetrosis, demonstrating the importance of fusion in osteoclast maturity and bone remodeling. In a recent study, we reported that Pin1 plays a role in the regulation of bone formation and Runx2 regulation. In this study, we explored the role of Pin1 in osteoclast formation and bone resorption. Pin1 null mice have l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 61 publications
0
52
0
Order By: Relevance
“…It was recently reported that Pin1 -/-mice exhibit a defect in bone morphogenetic protein signaling in osteoblasts but normal osteoclast function (Shen et al 2013). However, Islam et al (2014) demonstrated wide variation in the sizes of osteoclasts in Pin1 -/-mice, with very high numbers of large osteoclasts. Since Pin1 -/-mice show significant bone loss with aging ), we examined whether PIN1 is involved in osteoclast differentiation as well as up-regulation of osteoclastogenic cytokine expression in BMMs (the culmination of this process is periodontal bone destruction).…”
Section: Discussionmentioning
confidence: 93%
“…It was recently reported that Pin1 -/-mice exhibit a defect in bone morphogenetic protein signaling in osteoblasts but normal osteoclast function (Shen et al 2013). However, Islam et al (2014) demonstrated wide variation in the sizes of osteoclasts in Pin1 -/-mice, with very high numbers of large osteoclasts. Since Pin1 -/-mice show significant bone loss with aging ), we examined whether PIN1 is involved in osteoclast differentiation as well as up-regulation of osteoclastogenic cytokine expression in BMMs (the culmination of this process is periodontal bone destruction).…”
Section: Discussionmentioning
confidence: 93%
“…Pin1 KO mice were generated from heterozygous matings as described previously (28). All animal studies were reviewed and approved by the Special Committee on Animal Welfare, Seoul National University, Seoul, Republic of Korea.…”
Section: Methodsmentioning
confidence: 99%
“…Extraction of Total RNAs, RT-PCR, and Real-time PCR (Quantitative PCR)-Total RNA extraction from cultured cells, RT-PCR, quantitative PCR, and the primer sets for real-time PCR have been described previously (25,28).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prominent of these is DC‐STAMP (dendritic cell‐specific transmembrane protein) (Kukita et al, 2004; Yagi et al, 2005; Iwasaki et al, 2008; Mensah et al, 2010; Chiu et al, 2012; Chiu and Ritchlin, 2016), which has been identified as one of the most essential single factors supporting both differentiation and fusion. However, also other factors such as CD47 (Han et al, 2000; Lundberg et al, 2007; Maile et al, 2011; Koskinen et al, 2013; Hobolt‐Pedersen et al, 2014), syncytin‐1 (Soe et al, 2011), OC‐STAMP (osteoclast stimulatory transmembrane protein) (Miyamoto et al, 2012; Witwicka et al, 2015), dynamin (Shin et al, 2014; Verma et al, 2014), Pin1 (peptidyl‐prolyl cis‐trans isomerase NIMA‐interacting 1) (Islam et al, 2014; Cho et al, 2015), and e‐cadherin (Mbalaviele et al, 1995; Fiorino and Harrison, 2016) are involved in OC fusion, but it is important to stress that this list is not exhaustive. In order to identify the role of these factors , a series of molecular techniques, and cellular model systems have been employed, which in general are evaluated through end‐point measurements by counting the number of multi‐nucleated OCs, number of nuclei per OC, resorptive activity, and so forth at the end of the incubation period.…”
mentioning
confidence: 99%